Coated, Stabilized Enhanced-Efficiency Nitrogen Fertilizers: Preparation and Effects on Maize Growth and Nitrogen Utilization - Qi, Zenglian; Dong, Yuanjie; He, Mingrong; Wang, Maoying; Li, Yu; Dai, Xinglong (Frontiers in Plant Science, 2021)
Coated, slow/controlled release, or stabilized enhanced-efficiency nitrogen fertilizers (EENFs) are effective in improving nitrogen utilization efficiency (NUE) and crop yield. Better performance is expected from coated, stabilized EENFs where urease and nitrification inhibitors are treated in coated fertilizers. Firstly, five coated EENFs with different mass proportions of nature rubber (NR) in coating were prepared: CU0, CU1, CU2, CU3, CU4, and CU5 (0, 10, 20, 30, 40, and 50% of NR in coating). The controlled release performance of CU was tested by hydrostatic release test and the microstructure of controlled release urea, so as to screen the optimal addition ratio of NR (ER: NR = 7:3, CU3). Secondly, two coated, stabilized EENFs, CSU1 and CSU2, were prepared with natural rubber-modified epoxy resin (ER: NR = 7:3) as coating material. Seven treatments of different N fertilization were set up: CK (no N fertilization), urea, CU3, SU1, and SU2 (urease and nitrification inhibitors-treated urea fertilizers), CSU1 and CSU2 (urease and nitrification inhibitors-treated natural rubber-modified epoxy resin-coated urea fertilizers). Ammonia volatilization experiment and column leaching experiment showed that compared with conventional urea, NH3 volatilization loss was reduced by 20% and inorganic N leaching loss was reduced by 26% from CSU2, respectively. In the pot experiment, maize grain yield of 162.92 and 206.96 g/pot was achieved by CSU1 and CSU2, respectively, 41 and 79%, respectively, higher than that achieved by conventional urea. SUs treatments were more effective than conventional urea treatment in improving maize grain yield and NUE, but lower than in CSUs. The NUE, nitrogen fertilizer apparent utilization efficiency, partial factor productivity of applied N, and nitrogen utilization efficiency were 46, 30, 46, and 32%, respectively, higher in CSU1 and 58, 62, 58, and 29%, respectively, higher in CSU2 than in the conventional urea treatment. Compared with CSU1, CSU2 had better agronomic effectiveness with a higher NUE. It is recommended that urease and nitrification inhibitors be sandwiched between urea prill and the coating for preparation of novel, environmentally friendly coated, stabilized EENFs with high agronomic effectiveness, high NUE, and low N loss.